The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2193/2008-233
|View full text |Cite
|
Sign up to set email alerts
|

A Large‐Scale Mitigation Experiment to Reduce Bat Fatalities at Wind Energy Facilities

Abstract: Until large numbers of bat fatalities began to be reported at certain North American wind energy facilities, wildlife concerns regarding wind energy focused primarily on bird fatalities. Due in part to mitigation to reduce bird fatalities, bat fatalities now outnumber those of birds. To test one mitigation option aimed at reducing bat fatalities at wind energy facilities, we altered the operational parameters of 21 turbines at a site with high bat fatalities in southwestern Alberta, Canada, during the peak fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
136
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 16 publications
10
136
5
2
Order By: Relevance
“…Although our scope of inference is limited to certain tree bats (L. borealis, L. cinereus, and L. noctivagans), areas of turbines from the rotorswept zone around the nacelle to near the ground (different behaviors may occur higher in the airspace), and are based on observations from just three turbines in midwestern North America, efforts to monitor bat activity near turbines (e.g., acoustic detectors and video cameras), or deter bats from turbines [e.g., devices producing startling sounds (51)] may benefit by aiming instruments from the back of the nacelle into the leeward airspace, an area where we consistently observed higher bat activity regardless of changing wind directions. Strategies for minimizing fatalities of bats at turbines currently focus on preventing blades from spinning during low wind periods (4,11,12). Our observations that tree bats show a tendency to closely investigate inert turbines and sometimes linger for minutes to perhaps hours (in the cases of clustered observations) highlight the plausibility of a scenario in which bats are drawn toward turbines in low winds, but sometimes remain long enough to be put at risk when wind picks up and blades reach higher speeds.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although our scope of inference is limited to certain tree bats (L. borealis, L. cinereus, and L. noctivagans), areas of turbines from the rotorswept zone around the nacelle to near the ground (different behaviors may occur higher in the airspace), and are based on observations from just three turbines in midwestern North America, efforts to monitor bat activity near turbines (e.g., acoustic detectors and video cameras), or deter bats from turbines [e.g., devices producing startling sounds (51)] may benefit by aiming instruments from the back of the nacelle into the leeward airspace, an area where we consistently observed higher bat activity regardless of changing wind directions. Strategies for minimizing fatalities of bats at turbines currently focus on preventing blades from spinning during low wind periods (4,11,12). Our observations that tree bats show a tendency to closely investigate inert turbines and sometimes linger for minutes to perhaps hours (in the cases of clustered observations) highlight the plausibility of a scenario in which bats are drawn toward turbines in low winds, but sometimes remain long enough to be put at risk when wind picks up and blades reach higher speeds.…”
Section: Discussionmentioning
confidence: 86%
“…Fatalities during late summer and autumn tend to occur when average wind speeds are lower than about 5-6 m/s (4, 9, 10), and studies in Canada (11), the United States (12), and Germany (4) demonstrated that bat deaths can be substantially reduced by preventing turbine blades from turning until winds reach such speeds. Such operational modifications at wind facilities bring logistical and financial costs but may prove to be effective at reducing bat fatalities in many areas (11,12). Discovering the underlying reasons why bats are susceptible to wind turbines could help improve the efficiency of existing strategies and potentially uncover new ways of further reducing fatalities while maximizing power production.…”
mentioning
confidence: 99%
“…Some studies in North America and parts of Europe have documented migratory bats as being most at risk of collision with wind turbines (Du¨rr & Bach 2004;Kunz 2004;Pasqualetti et al 2004;Baerwald et al 2009), but other studies from Europe did not find this pattern (Rydell et al 2010b). Rydell et al (2010a,b) found that the bat genera at most risk of colliding with wind turbines in northwest Europe were Nyctalus, Pipistrellus and Vespertilio and to some extent also Eptesicus, all of which have long and narrow wings, forage in the open air and tend to be migratory.…”
Section: Discussionmentioning
confidence: 99%
“…However, most fatalities occur during low wind nights (<6 m/s) in late summer and the fi rst half of autumn, thus increasing the cut-in speed of the turbines on nights with high risk of bat collision would be an effective management tool to reduce mortality. Indeed, these methods have achieved reductions of bat fatalities from 50 to 90 % with marginal power loss (≤ 1 % of total annual output) (Baerwald et al 2009 ;Arnett et al 2011 ). Conversely, other management measures such as acoustic deterrents are less effective, in part due to rapid atmospheric attenuation of ultrasounds (Arnett et al 2013 ).…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 99%